Presence of bacteria in modified atmosphere packed raw chicken meat and their effect on shelf life and sensory characteristics : a microbiological and sensory evaluation - Peterson, Max (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2022)
Food waste is a huge challenge and constitutes a massive hurdle for development of sustainable food systems. Around 30% of all food produced for human consumption globally is estimated to be discarded, which in many cases is due to the foods having reached best-before-date. Bacterial groups such as Total aerobic count (TAC), Lactic acid bacteria (LAB) and Enterobacteriaceae (EB) are important quality indicators or spoilage bacteria of many food items, for example fresh and perishable foods such as chicken or minced meat. The aim of this study is to evaluate if the shelf life of chicken breast fillet can be extended by analyzing bacterial levels and sensory characteristics of chicken. In the present study, chicken breast fillets were analysed at three different time points; EXP (day or expiration), EXP+2 (2 days past expiration date) and EXP+4 (4 days past expiration date) at two different storage temperatures (4°C and 8°C) to see changes in growth of different bacterial populations over time from established expiration date up to 4 days past expiration date. In addition, two sensory evaluations were performed to evaluate flavor, odor and texture at the three different time points. The results from the microbiological study were compared to the sensory evaluation results in order to investigate the potential to extend the shelf life of chicken without compromising sensory characteristics. The highest population of TAC (8.1 log CFU/g) was found in chicken breast fillets stored at 8°C and analysed 4 days after expiration date. Chicken breast fillets that had been stored at 4°C and analysed at expiration date had the lowest TAC levels (5.9 log CFU/g). However, the sensory evaluations showed that none of the chicken breast fillets tested was significantly different to the other. This means that chicken with prolonged shelf life (and with TAC 8.1 log CFU/g) was consumable and had no significant effect on flavor, odor or texture of the cooked product compared to chicken consumed at expiration date. Further research needs to be conducted to extend the shelf life of raw chicken breast fillets, and to establish a scientific foundation for appliance and use of dynamic food labels to reach the long-term goal of reducing food waste.